Evaluation of tribological properties of sesame oil as biolubricant with SiO2 nanoparticles and imidazolium-based ionic liquid as hybrid additives. (September 2019) - Sabarinath, S; Rajendrakumar, PK; Prabhakaran Nair, K
The renewability and ecofriendly nature of vegetable oils make them a competitive candidate to replace depleting petroleum-based mineral oils. However, the poor antiwear properties of vegetable oils restrict them from many industrial applications as lubricants. In the present work, the synergic effect of SiO2 nanoparticles with ionic liquids 1-butyl-3- methylimidazolium tetrafluoroborate and 1-hexyl-3-methylimidazolium tetrafluoroborate as hybrid antiwear additives in enhancing the tribological properties of sesame oil is studied for steel on steel contacts. Morphologies of the worn surfaces and possibilities of tribofilm formation are examined using a field-emission scanning electron microscope and energy-dispersive spectroscopy analysis. A density functional theory analysis is performed to study the existence of intermolecular forces of attraction between ionic liquid and triglyceride molecules. Rheological properties of the blends are evaluated using Anton Paar MCR10 rheometer. Corrosive properties of the oil blends are studied using copper strip corrosion test (ASTM D130).